Simultaneous determination of seven perfluoroalkyl carboxylic acids in water samples by 2, 3, 4, 5, 6-pentafluorobenzyl bromide derivatization and gas chromatography-mass spectrometry. (November 2020) - Ji, Yongyan; Cui, Zongyan; Wang, Zhibin; Cao, Yanzhong; Li, Xuemin; Li, Adan
Abstract: A new derivatization reagent, 2, 3, 4, 5, 6-pentafluorobenzyl bromide (PFBBr), was employed to determine seven perfluoroalkyl carboxylic acids (PFCAs) simultaneously in tap water with gas chromatography-mass spectrometry (GC-MS) technique in this study. Firstly, seven PFCAs were derivatized to their corresponding esters under alkaline condition. The derivatization conditions including the amount of PFBBr and K2 CO3, derivatization temperature and time were optimized to increase the derivatization efficiency. The 14 tap water samples collected from different places of China were enriched and purified through solid phase extraction pretreatment. The limits of detection (LODs) and the limits of quantitation (LOQs) ranged from 0.1 ng/L to 0.28 ng/L and from 0.3 ng/L to 0.84 ng/L, respectively. The new method offers a linear relationship in the range from 2 ng/L to 2000 ng/L, and the correlation coefficients ranged from 0.9938 to 0.9994. The results showed that GC-MS combined with pre-column derivatization is a reliable method for the analysis of PFCAs in the aqueous environment. Graphical abstract: Image 1 Highlights: Determination of 7 PFCAs with PFBBr derivatization was developed for the first time. This method has the lower LODs compared to the published literatures determined PFCAs with GC-MS. The application of this method was checked using 14 tap water in China, and four PFCAs were detected in the range from 4.5 ng/L to 15.1 ng/L. Abstract : 2, 3, 4, 5, 6-Pentafluorobenzyl bromide (PFBBr) was employed as a new derivatization reagent to analyze seven perfluoroalkyl carboxylic acids (PFCAs).